Stakeholder Participation Targets the Rural Poor : China Basic Health Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
The past 20 years have witnessed a growing disparity in health status indicators between urban and rural populations in China. The economic and social reforms that have accelerated the growth in GDP and personal income levels of the urban population have not trickled down to the rural areas. Declining government support of public health programs and the collapse of community financing of health services have meant that health services in poor rural areas have deteriorated in general. Services have declined in coverage, quality, efficiency, utilization, and financial viability. To address this disparity, the World Bank-supported Basic Health Project in China introduced a systematic but rapid process of consultation and feedback among selected beneficiary communities. The project was prepared using guidelines prepared by national and international experts. The social assessment confirmed impressions gained from less structured consultations and provided additional support for project design. Stakeholder involvement was extensive, including consultations with governmental departments of planning, finance, poverty alleviation, personnel, and education, as well as civil society groups such as the All China Women's Federation and the Red Cross. Field visits included focus group discussions with local government representatives, village officials, and householders. The rural poor, including minority nationalities, figured prominently in such consultations. This note concludes that responsive social development has its risks. Even in such an innovative and comprehensive project, maintaining a balance between improvement of health facilities versus population-based health care remains a challenge. Without adequate technical support and supervision, or without adequate funds in the county poverty fund to reimburse health care providers for their services given to the poor, this balance could ultimately break down and erode the lines of communication and trust established by the project.